Activity of fungicide mixtures against Botrytis cinerea isolates resistant to benzimidazoles, strobilurins and dicarboximides. (27th February 2019) - Ebrahimzadeh, Fatemeh; Abrinbana, Masoud
Abstract : Botrytis cinerea, the causal agent of grey mould in a broad range of crops, is considered a high‐risk plant pathogen for fungicide resistance development. The use of fungicide mixtures, particularly combinations with synergistic activity, can be a useful tactic to counteract resistance build‐up in pathogen populations. The present study aimed to investigate the effects of different ratios of two‐way mixtures of carbendazim, iprodione, kresoxim‐methyl, tebuconazole and penconazole on four B. cinerea isolates that were sensitive or resistant to benzimidazoles, dicarboximides and strobilurins. The isolates that were resistant to benzimidazoles and strobilurins had E198A and G143A mutations in β‐tubulin and cytochrome b genes, respectively. The mixtures had different effects on each of the isolates in vitro but, in 13 combinations, the synergistic effect was observed against all or three isolates. In greenhouse experiments, 11 fungicide combinations used in decreased (EC75 ) concentrations showed the maximum control efficiency. The two follow‐up greenhouse experiments using six selected combinations revealed they were highly effective against additional isolates with various fungicide resistance profiles. The identified mixtures‐ratios have potential for use in grey mould management programs in the greenhouse. Abstract : In the present study, we investigated the effects of different ratios of all possible two‐way mixtures of carbendazim, iprodione, kresoxim‐methyl, tebuconazole and penconazole on four B. cinera isolates that were sensitive or resistant to benzimidazoles, dicarboximides and strobilurins. The mixtures had different effects on each of the isolates in vitro but, in 13 combinations, the synergistic effect was observed against all or three isolates. In greenhouse experiments, 11 fungicide combinations used in decreased (EC75 ) concentrations showed 100% control efficiency.